Formação em fisioterapia no Estado de São Paulo : uma análise de cursos públicos à luz das Diretrizes Curriculares Nacionais - Sasaki, Katia Tamae (Universidade Federal de São Carlos, 2017)
The present study had as objective to analyze how the National Curricular Guidelines (DCN) are contemplated in the Pedagogical Projects of Courses (PPC) of graduation in Physical Therapy of the Public Universities of the State of São Paulo as well as the perception by the coordinators of the courses. It is a research of a qualitative nature, with an interpretive-explanatory purpose. The PPCs of the five courses were analyzed through a documentary collection and, later treated through a documentary analysis according to the analytical categories constructed as a methodological tool of a platform of research from two axes: Curriculum and Professional Profile. The collection also included the semi structured interview with the coordinators of the Physiotherapy courses was composed of questions that elucidated how the assumptions of the DCN present in the PPC applies in the curricular activities. The information collected in the interviews was analyzed according to Content Analysis (CA) in the thematic analysis modality. The Curricular Axis was able to demonstrate that most curricula reflect conservative conceptions, organized by fragmented disciplines as well as didactic activities and traditional learning methodologies; Basically consisting of learning processes based on the transmission of knowledge with a biological focus on health, with a predominance of the reproduction of hegemonic practices of the traditional approach to knowledge, through teacher-centered teaching methodologies, which does not articulate with the profile of the Egress and professional profile present in PPCs. Two PPCs, however, have built strategies throughout their curricular implementation process, advancing the proposals of the DCN, one of which informs that it seeks to articulate the disciplinary educational object for the development of competence, to promote changes in professional practices with models of overcoming the traditions derived from the minimal curricula, in the challenge of constructing an innovative pedagogical project. In the Professional Profile the courses contemplate in their PPC the professional profile advocated by the DCN and some indicate a greater focus for the area of the health care having the SUS as a great scenario and in relation to the Management in Health and Education in Health most of the courses only report these categories in the objectives of the course. The report of the coordinators was fundamental for critical reflection, deepening the analysis of how this formation has been occurring and indicate the current situation of curricula that require reformulation and updates that promote changes in professional practices.
Keywords: Diretrizes curriculares nacionais; Projeto pedagógico de curso; Fisioterapia; National curricular guidelines; Pedagogical course project; Physiotherapy; CIENCIAS DA SAUDE